The First 18 Months of JGR: MLC - Enrico Camporeale; Raffaele Marino; John Rundle; Doris Folini; Yangkang Chen; Donald D. Lucas; Xiaofeng Li; Thomas E. Berger; Geoffrey C. Fox; Yixin Wen; Chaopeng Shen; Renata Wentzcovitch (Journal of Geophysical Research: Machine Learning and Computation, 2025)
Abstract As editors of Journal of Geophysical Research: Machine Learning and Computation, we are delighted to celebrate the successes of our first 18 months.